The Form and Function of Prayer in the Student Volunteer Movement, 1886–1914. (August 2019) - Allen, Edward
Abstract : The founders of the Student Volunteer Movement for Foreign Missions (SVM) repeatedly affirmed that prayer as a means of accessing the power of the Almighty God was at the foundation of its success. An examination of original sources for the SVM shows that many forms of prayer were practised and encouraged by the movement. Members of the movement sought to make formal prayer meaningful. Participants described how their prayers for provision were answered along the lines of the faith ministries of George Muller and Hudson Taylor. They described how prayer enabled them to be connected to other Christians from around the world. Prayer enabled them to experience community support and was the focus of personal communion with God. However, the prayer of surrender was at the heart of the SVM experience and finds a parallel in the experience of a 'second blessing' advocated by the Keswick Movement. Numerous points of contact occurred between the SVM and Keswick, suggesting that second-blessing experience of holiness prepared a person for the commitment represented by signing the SVM pledge to give oneself in the service of foreign missions.